(untitled) (Herald of Journalism, 2021)
The article is devoted to the urgent problem of national identity, within the available information space. Monitoring of foreign publications revealed tendencies to unreasonably narrow or limit the impor- tance of the works of geniuses of scientific thought to ethnic boundaries. Using al-Farabi’s identification as an example, the author identifies and classifies system trends that demonstrate the duplication in time and space of “algorithms” that may contradict each other in the light of ideological concepts. Methods and materials relied on the basic principles of dialectics, logic and induction, comparative analysis and interdisciplinarity, in order to determine the subjective and objective factors of the forma- tion of national identity. The materials for the research were taken from sources obtained by means of digital technologies from the sites of foreign library funds and archival depositories of foreign research centers. We studied an array of thematic publications in English on Farabi studies in foreign countries. Digital copies of the publications of interest to us are indicated in the links. Scientific originality of the research lies in the detection of a complex of subjective and objective factors that influenced the external “design” of the identity of such an author of scientific treatises as al-Farabi in the context of different cultures. A comparative study of Western European, USA, Maghreb states, Central Asian and Eastern European references to the medieval thinker and written evidence in the format of a catalog in archival funds and scientific collections in order to identify possible conscious and imaginary discrepancies in the identification of ethnic origin and successors of al-Farabi, in our opinion, implemented for the first time. Practical significance is important to revive the “inaccuracies” and “conventions” previously admit- ted from outside in identifying the Turks of the Great Steppe and their real role in intercultural contacts. Key words: al-Farabi, philosopher, Turks, identity, Great Steppe, sources.